Somatosensory profiles in patients with non-specific neck-arm pain with and without positive neurodynamic tests. (December 2020) - Ottiger-Boettger, Karina; Ballenberger, Nikolaus; Landmann, Gunther; Stockinger, Lenka; Tampin, Brigitte; Schmid, Annina
Abstract: Despite normal neurological integrity tests, some patients with non-specific neck-arm pain (NSNAP) have heightened nerve mechanosensitivity upon neurodynamic testing. The aim of this study was to determine whether or not a nerve dysfunction is present in patients with positive neurodynamic tests compared to those with negative neurodynamic tests or healthy controls. Somatosensory profiling using quantitative sensory testing (QST) was established in 40 consecutive patients with unilateral NSNAP; 23 had positive upper limb neurodynamic tests (ULNTPOS ) and 17 had negative neurodynamic tests (ULNTNEG ) and in 26 healthy controls. QST included measurement of thermal and mechanical detection and pain thresholds in the maximal pain area on the symptomatic side as well as the corresponding contralateral area. Fifty-seven percent of patients with NSNAP had positive neurodynamic tests. Somatosensory profiling revealed a loss of function phenotype in NSNAP patients compared to healthy controls both in the maximal pain area and asymptomatic side. Hyperalgesia (cold, heat and pressure) was present bilaterally in both NSNAP groups. Direct comparison between the patient groups revealed no significant differences in somatosensory profiles. However, the ULNTPOS group demonstrated sensory loss compared to healthy controls in more parameters than the ULNTNEG group. The ULNTNEG subgroup represented an intermediate phenotype between ULNTPOS patients and healthy controls in most detection thresholds as well as thermal and pressure pain thresholds. Even though patients with NSNAP present as a spectrum, it remains unclear whether the sensory changes are indicative of a nerve dysfunction/lesion or rather a marker of altered central pain processing. Highlights: 57% of patients with NSNAP have positive neurodynamic tests (NT). Patients with NSNAP have bilateral somatosensory hypoaesthesia and hyperalgesia. Patients with negative and positive NT have comparable sensory function. Patients with positive NT demonstrated sensory loss in more parameters. NSNAP presents as a spectrum of nerve dysfunction/lesion or central changes.